The Elliptical Aggregates – Idiopathic Granulomatous Mastitis - Bajaj, Anubha (International Journal of Infection Prevention, 2020)
Idiopathic granulomatous mastitis was initially scripted in 1972 by Kessler and Wolloch and is cogitated as an infrequent, benign, chronic inflammatory disorder. It commonly implicates females of reproductive age group, especially women who have breast fed in the preceding five to six years. Idiopathic granulomatous mastitis is commonly discerned in Asia and Mediterranean region although true incidence is undetermined. Diverse ethnicities delineate a diverse disease prevalence. Elimination of adjunctive causes of granulomatous inflammation makes idiopathic granulomatous mastitis a diagnosis of exclusion. As per the natural history, idiopathic granulomatous mastitis is designated as a self limiting disorder 1.
Keywords: Chronic; disease; disorder; diagnosis